An Acute Reduction in Habitual Protein Intake Attenuates Post Exercise Anabolism and May Bias Oxidation-Derived Protein Requirements in Resistance Trained Men - Tinline-Goodfellow, Cassidy T.; West, Daniel W. D.; Malowany, Julia M.; Gillen, Jenna B.; Moore, Daniel R. (Frontiers in Nutrition, 2020)
Protein recommendations for resistance-trained athletes are generally lower than habitual intakes. Excess protein consumption increases the capacity to oxidize amino acids, which can attenuate post-exercise anabolism and may impact protein requirements determined by stable isotope techniques predicated on amino acid tracer oxidation. We aimed to determine the impact of an acute (5d) reduction in dietary protein intake on post-exercise anabolism in high habitual consumers using the indicator amino acid oxidation (IAAO) technique. Resistance trained men [n=5; 257 y; 73.05.7 kg; 9.92.9% body fat; 2.690.38 g·kg-1·d-1 habitual protein intake) consumed a high (H; 2.2 g·kg-1·d-1) and moderate (M; 1.2 g·kg-1·d-1) protein diet while training every other day. During the High protein phase, participants consumed a 2d controlled diet prior to determining whole body phenylalanine turnover, net balance (NB), and 13CO2 excretion (F13CO2) after exercise via oral [13C]phenylalanine. During the Moderate phase, participants consumed 2.2 g protein·kg-1·d-1 for 2d prior to consuming 1.2 g protein·kg-1·d-1 for 5d. Phenylalanine metabolism was measured on days 1, 3 and 5 (M1, M3, and M5, respectively) of the moderate intake. F13CO2, the primary outcome for IAAO, was 72% and 55% greater on the first day (M1, P<0.05) and the third day of the moderate protein diet (M3, P=0.07), respectively, compared to the High protein trial. Compared to the High protein trial, NB was 25% lower on the first day (M1, P<0.01) and 15% lower on the third day of the moderate protein diet (M3, P=0.09). High habitual protein consumption may bias protein requirements determined by traditional IAAO methods that use only a 2d pre-trial controlled diet. Post-exercise whole body anabolism is attenuated following a reduction in protein intake in resistance trained men and may require 3-5d to adapt. This trial is registered at clinicaltrials.gov as NCT03845569.